Effects of mindfulness-based stress reduction on psychological distress in health workers: A three-arm parallel randomized controlled trial. (January 2022) - Errazuriz, Antonia; Schmidt, Kristin; Undurraga, Eduardo A.; Medeiros, Sebastián; Baudrand, Rene; Cussen, Diego; Henriquez, Marcela; Celhay, Pablo; Figueroa, Rodrigo A.
Abstract: Mindfulness-based Stress Reduction (MBSR) has shown good efficacy for improving wellbeing in employees experiencing occupational stress. However, comparisons with other interventions, longer-term follow-up, and data from varying sociocultural contexts are lacking. This three-arm, parallel randomised controlled trial (RCT) examined the effects of MBSR on psychological distress in non-physician health workers in direct contact with patients. 105 participants were randomly allocated to either: (1) MBSR (N = 35), (2) Stress Management Course (SMC; N = 34) or (3) wait-list (N = 36). Participants and those assessing outcomes were blinded to group assignment. Participants completed questionnaires pre- and post-intervention and four months after the intervention. Psychological distress was measured using the General Health Questionnaire (GHQ-12) and Outcome Questionnaire (OQ-45). Secondary outcomes included perceived stress, job satisfaction, mindfulness skills and changes in salivary cortisol. 77 participants completed measures post-intervention and 52 at 4-month follow-up. MBSR showed a post-intervention effect in reducing GHQ-12 (ß = −0.80 [SE = 1.58] p  < 0.01) and OQ-45 (ß = −0.72, [SE = 5.87] p  < 0.05) psychological distress, compared to SMC and in reducing GHQ-12 (ß = −1.30 [SE = 1.38] p  < 0.001) and OQ-45 (ß = −0.71, [SE = 5.58] p  < 0.01) psychological distress compared to wait-list condition. In our secondary outcome, only MBSR was associated with a decrease in the cortisol awaking response by 23% ( p  < 0.05). At follow-up, only effects of MBSR on the psychological distress 'social role' subscale (ß = −0.76 [SE = 1.31] p < 0.05) remained significant, compared to SMC. In conclusion, MBSR appears useful in reducing short-term psychological distress in healthcare workers, but these effects were not maintained at follow-up. Trial registration: ISRCTN12039804. Highlights: Three-arm randomised controlled trial from Chile targeting occupational stress. Mindfulness-based stress reduction reduces psychological distress in health workers. Reduction in psychological distress not found in psychoeducation or waitlist groups. Mindfulness intervention only associated with reductions in salivary cortisol. Weak effects at follow-up suggests crucial to target maintenance of benefits.